Multistatic Specular Meteor Radar Network in Peru: System Description and Initial Results. Issue 1 (13th January 2021) - Chau, J. L.; Urco, J. M.; Vierinen, J.; Harding, B. J.; Clahsen, M.; Pfeffer, N.; Kuyeng, K. M.; Milla, M. A.; Erickson, P. J.
Abstract: The mesosphere and lower thermosphere (MLT) region is dominated globally by dynamics at various scales: planetary waves, tides, gravity waves, and stratified turbulence. The latter two can coexist and be significant at horizontal scales less than 500 km, scales that are difficult to measure. This study presents a recently deployed multistatic specular meteor radar system, SIMONe Peru, which can be used to observe these scales. The radars are positioned at and around the Jicamarca Radio Observatory, which is located at the magnetic equator. Besides presenting preliminary results of typically reported large‐scale features, like the dominant diurnal tide at low latitudes, we show results on selected days of spatially and temporally resolved winds obtained with two methods based on: (a) estimation of mean wind and their gradients (gradient method), and (b) an inverse theory with Tikhonov regularization (regularized wind field inversion method). The gradient method allows improved MLT vertical velocities and, for the first time, low‐latitude wind field parameters such as horizontal divergence and relative vorticity. The regularized wind field inversion method allows the estimation of spatial structure within the observed area and has the potential to outperform the gradient method, in particular when more detections are available or when fine adaptive tuning of the regularization factor is done. SIMONe Peru adds important information at low latitudes to currently scarce MLT continuous observing capabilities. Results contribute to studies of the MLT dynamics at different scales inherently connected to lower atmospheric forcing and E‐region dynamo related ionospheric variability. Plain Language Summary: The mesosphere and lower thermosphere (MLT) region is dominated by neutral wind dynamics with structure scales ranging from a few thousands of kilometers down to a few kilometers. In this work, we present a new state‐of‐the‐art ground‐based radar system using multistatic meteor scattering that allows tomographic studies of MLT wind dynamics at scales not possible before. Given the location of the radar network at the magnetic equator, its focus is on wind dynamics peculiar to equatorial latitudes. Two methods for estimating the mesospheric neutral wind field are used. One takes into account wind gradients in addition to mean wind (gradient method). The other estimates a spatially resolved wind vector field and uses an additional mathematical constraint that produces smooth wind field solutions (regularized wind field inversion method). Using the gradient method, the vertical wind estimate is improved. For the first time at MLT equatorial latitudes, parameters familiar to meteorologists, such as horizontal divergence and relative vorticity are obtained. Measurements from this new system have the potential to contribute to coupling studies of the atmosphere and the ionosphere at low latitudes. Key Points: Measurements of horizontal wind gradients at low‐latitude mesosphere and lower thermosphere altitudes These gradients of the horizontal winds show strong temporal and altitude variability that are not observed at high latitudes Improved vertical winds are obtained using a gradient wind field method inherently free from horizontal divergence contamination